pengaruh persepsi siswa tentang profesionalisme guru, lingkungan sekolah dan motivasi belajar terhadap hasil belajar ekonomi siswa kelas X di SMA N 6 sijunjung (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2017)
ABSTRACT The results showed 1). Teacher professionalism positive and significant effect on the results of class X student of economic subjects in high school N 6 Sijunjung, shown by the path coefficient value of 0.289. This coefficient value siginfikan where t count 5,283> t table amounted to 1.989686. 2). The school environment positive and significant effect on the results of class X student of economic subjects in high school N 6 Sijunjung, shown by the path coefficient value of 0.450. This coefficient value siginfikan where t value of 8.524> t table amounted to 1.989686. 3). Teacher professionalism and significant positive effect on the motivation of class X student in high school N 6 Sijunjung, shown by the path coefficient value of 0.367. This coefficient value siginfikan where t value of 3.782> t table amounted to 1.989686. 4). School Environment and significant positive effect on the motivation of class X student in high school N 6 Sijunjung, shown by the path coefficient value of 0.261. This coefficient value siginfikan where t count of 2.691> t table amounted to 1.989686. 5). Students' motivation positive and significant effect on the results of class X student high school N 6 Sijunjung, shown by the path coefficient value of 0.437. This coefficient value siginfikan where t count of 7.729> t table of 1.989686. Keywords: Professional Teacher, School Environment, Motivation ABSTRAK Hasil penelitian menunjukan 1). Profesionalisme guru berpengaruh positif dan signifikan terhadap hasil belajar siswa X mata pelajaran ekonomi di SMA N 6 Sijunjung, yang ditunjukan oleh nilai koefisien jalur sebesar 0,289. Nilai koefisien ini siginfikan dimana nilai thitung 5,283 > ttabel sebesar 1.989686. 2). Lingkungan sekolah berpengaruh positif dan signifikan terhadap hasil belajar siswa kelas X mata pelajaran ekonomi di SMA N 6 Sijunjung, yang ditunjukan oleh nilai koefisien jalur sebesar 0,450. Nilai koefisien ini siginfikan dimana nilai thitung sebesar 8,524 > ttabel sebesar 1.989686. 3). Profesionalisme guru berpengaruh positif dan signifikan terhadap motivasi belajar siswa kelas X di SMA N 6 Sijunjung, yang ditunjukan oleh nilai koefisien jalur sebesar 0,367. Nilai koefisien ini siginfikan dimana nilai thitung sebesar 3,782 > ttabel sebesar 1.989686. 4). Lingkungan Sekolah berpengaruh positif dan signifikan terhadap motivasi belajar siswa kelas X di SMA N 6 sijunjung, yang ditunjukan oleh nilai koefisien jalur sebesar 0,261. Nilai koefisien ini siginfikan dimana nilai thitung sebesar 2,691 > ttabel sebesar 1.989686. 5). Motivasi belajar siswa berpengaruh positif dan signifikan terhadap hasil belajar siswa kelas X SMA N 6 Sijunjung, yang ditunjukan oleh nilai koefisien jalur sebesar 0,437. Nilai koefisien ini siginfikan dimana nilai thitung sebesar 7,729 > ttabel sebesar 1.989686. Kata kunci: Profesionalisme Guru, Lingkungan Sekolah, Motivasi Belajar